Pengaruh Religiusitas dan Machiavellian terhadap Kecenderungan Kecurangan Akuntansi - Ninda Vacumi; Halmawati Halmawati (Jurnal Eksplorasi Akuntansi, 2022)
The purpose of this study was to determine the effect of religiosity and machiavellianism on the tendency of accounting fraud. The population in this survey is the work unit of regional apparatus organizations in the Lima Puluh Kota Regency, totaling 27 SKPD, and the interviewees are office managers, managers of finance divisions, and technical implementers of each SKPD. The research design in this study is a quantitative approach using primary data. Primary data was obtained by distributing the survey directly to 81 respondents. We then analyzed the data using multiple linear regression techniques. The results of this study are (1) religiosity has a negative and significant effect on the tendency of accounting fraud in the Regional Apparatus Work Unit (SKPD) of Lima Puluh Kota Regency, (2) Machiavellian has a positive and significant effect on the tendency of accounting fraud in the regional work unit (SKPD) of Lima Puluh Kota Regency.